Musical Performance Anxiety and Voice Handicap in Amateur Evangelical Singers - Silva, Ana Maria Costa; Depolli, Gabriel Trevizani [UNESP]; Azevedo, Elma Heitmann Mares; Moreti, Felipe [UNESP]; Guimarães, Michelle Ferreira (Elsevier, 2024)
Objective: To compare and correlate musical performance anxiety (MPA) and vocal self-perception among amateur evangelical singers, focusing on the interaction between anxiety and aspects of performance in this sample. Method: This study employed a cross-sectional and quantitative approach, involving 75 amateur gospel singers from evangelical churches, aged between 18 and 59 years. Data collection included the administration of a sample identification and characterization questionnaire, the Brazilian Portuguese version of the Kenny Music Performance Anxiety Inventory (K-MPAI), and the Singing Voice Handicap Index (S-VHI). The descriptive analysis used absolute and relative frequencies, measures of central tendency, and dispersion (mean and standard deviation [SD]). To compare the vocal self-assessment protocols and performance aspects, the Kruskal-Wallis test was applied. Spearman's correlation test was used for correlation analysis. All analyses were conducted with a significance level set at 5% (P < 0.05). Results: Vocal warm-up and cool-down activities, vocal discomfort after performance, and vocal self-assessment were significantly associated with scores on S-VHI, and the variable “instruments louder than voices” was associated with the K-MPAI score. Participants exhibited a mean K-MPAI score of 85.12 points (SD ± 36.6), and the vocal handicap of the sample had a mean score of 45.22 (SD ± 32.3). There was no statistically significant correlation between the protocols. Conclusion: Incorporating vocal warm-up and cool-down activities was significantly associated with lower scores on S-VHI. Conversely, those experiencing postperformance vocal discomfort exhibited higher scores on S-VHI. Moreover, the absence of correlation between the assessment protocols suggests that while significant levels of voice handicap were observed, a direct link to MPA cannot be definitively established. Overall, these findings contribute to a nuanced understanding of the multifaceted factors shaping vocal health and performance among amateur evangelical singers, thereby guiding future research and interventions in this field.
Keywords: Anxiety; Language and hearing sciences; Performance; Singing; Speech; Voice